Tunisia : From Revolutions to Institutions - Brisson, Zack; Krontiris, Kate (World Bank, Washington, DC, 2017)
In the wake of the revolution, Tunisian society is currently undergoing a significant transformation. In late 2011, the country's first representative government in more than three decades was formed, as the Constituent Assembly was seated. Hundreds of legitimate candidates ran in an election that was free, fair, and enjoyed nearly 90 percent participation by eligible voters. 'Tunisia: from revolutions to institutions,' published one year after the exile of Ben Ali, seeks to describe the factors driving this transformation, examining how specific elements of society have changed, or not changed, in the post-revolutionary period. Information and communication technologies (ICTs), which played a central role in the lead-up to the revolution as well as the revolution itself, have continued to influence rapid changes in the past year. This report charts the application of these technologies by citizens, civil society, entrepreneurs, and government stakeholders. It also identifies openings to capitalize on technology's ability to improve governance, expand economic opportunity, and encourage social cohesion.